Regulation of the Sar1 GTPase Cycle Is Necessary for Large Cargo Secretion from the Endoplasmic Reticulum - Saito, Kota; Maeda, Miharu; Katada, Toshiaki (Frontiers in Cell and Developmental Biology, 2017)
Proteins synthesized within the endoplasmic reticulum (ER) are transported to the Golgi via coat protein complex II (COPII)-coated vesicles. The formation of COPII-coated vesicles is regulated by the GTPase cycle of Sar1. Activated Sar1 is recruited to ER membranes and forms a pre-budding complex with cargoes and the inner-coat complex. The outer-coat complex then stimulates Sar1 inactivation and completes vesicle formation. The mechanisms of forming transport carriers are well conserved among species; however, in mammalian cells, several cargo molecules such as collagen and chylomicrons are too large to be accommodated in conventional COPII-coated vesicles. Thus, special cargo-receptor complexes are required for their export from the ER. cTAGE5/TANGO1 complexes and their isoforms have been identified as cargo receptors for these macromolecules. Recent reports suggest that the cTAGE5/TANGO1 complex interacts with the GEF and the GAP of Sar1 and tightly regulates its GTPase cycle to accomplish large cargo secretion.